Prospective writing: Randomized controlled trial of an intervention for facilitating growth after adversity. Issue 6 (2nd November 2018) - Roepke, Ann Marie; Benson, Lizbeth; Tsukayama, Eli; Yaden, David Bryce
Abstract: Little is known about how posttraumatic growth (PTG) can be fostered and controversy surrounds how it is best measured. We designed and tested an intervention, prospective writing, to facilitate PTG by encouraging people to explore new possibilities after adversity. Adults ( N = 188) with recent adverse experiences were randomly assigned to do prospective writing, factual writing, or no writing weekly for one month. PTG was assessed with both retrospective and current-standing measures. Hierarchical linear modeling and response profile analysis were used to assess the intervention's impact, and latent growth curve modeling was used to test mediation. Prospective writing participants showed the greatest gains in PTG as assessed by the current-standing measure, but did not reliably show greater retrospective PTG than controls. Although large effect sizes for the mediation paths suggested that engagement with new possibilities may be a plausible mechanism, this result fell short of statistical significance. Prospection-based interventions merit further investigation.